Social Ineptitude as the Core of Politics in Nigeria: A Reading from Adamu Kyuka Usman’s Hope in Anarchy - Jighjigh Leo Justus, Ishima; K. Ukande, Chris (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The 21st century Nigeria still retains all the nefarious activities that have characterised the previous administrations even though it has clocked 60 years of independence. No doubt, Nigeria has proven and still proves that the nomenclature that it has earned for itself as “Giant of Africa”, is true not only in its size as a country but also in its draconian, unscrupulous and incongruous disposition. Adamu Kyuka Usman in his Hope in Anarchy unveils such ills. This paper therefore, examines social ineptitude as the core of politics in Nigeria. The paper adopts the qualitative research methodology using primary and secondary sources in carrying out this task. The study identifies that the positive dreams of Nigerians that led them to vote the present administration into power, have been kept in limbo due to malfunction. The study depicts in totality, the dastardly acts of political gladiators and at the same time, showcases the sort of debased and dehumanised life being experienced by the downtrodden of the Nigerian society. The paper concludes that unless the ordinary Nigerians are given the opportunity by the ruling class, to really show that blood flows in their veins because they are humans, there is just no way that there would be peace, tranquility and progress, hence, Nigeria retaining its status of political waste land.